The Effect of Profitability and Firm Size on Financial Performance in Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock - Dwi Yuni Martaulina; Andi Afrizal; Arfianti Novita Anwar; Teresa Freitas Belo (International Journal of Economic and Tourism Research, 2026)
This study aims to examine the effect of profitability and firm size on financial performance in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research adopts a quantitative approach using secondary data derived from annual financial statements. From a population of sixteen companies, eight firms were selected through purposive sampling, resulting in 40 firm-year observations. Profitability is proxied by Net Profit Margin (NPM), firm size is measured by total assets, and financial performance is proxied by Return on Assets (ROA). Data were analyzed using multiple linear regression after passing classical assumption tests, including normality, heteroscedasticity, multicollinearity, and autocorrelation tests. The results indicate that profitability has a positive and significant effect on financial performance. Firm size also demonstrates a positive and significant influence on financial performance. Simultaneously, profitability and firm size significantly explain variations in ROA, with an adjusted R² value of 0.428, indicating moderate explanatory power. These findings support signalling theory, suggesting that profitability and firm size function as important signals reflecting operational efficiency and financial stability. The study contributes empirical evidence regarding the determinants of financial performance in Indonesia’s food and beverage manufacturing sub-sector and provides practical implications for corporate management and investors.